THE ROLE OF THE EMOTIONAL FACTOR IN THE EDUCATIONAL AND COGNITIVE ACTIVITY OF FUTURE TEACHERS - Sadokhina К.С. (Pedagogy of Higher and Secondary Education, 2011)
The article explains the role of emotional factors in educational-cognitive activity of students - future teachers. Reveals the "emonational core" of the structural components of the educational-cognitive activity: substantive, procedural and motivational, whici function in a coherent system.